Targeting circulating tumor cell‒neutrophil interactions: nanoengineered strategies for inhibiting cancer metastasis - Yong Su; Mingjing Leng; Qingqing Yang; Wenbi Jiang; Gang Xiang; Ling Long; Xing Zhou (Journal of Nanobiotechnology)
Abstract Metastasis remains the leading cause of cancer-related mortality, with a persistently poor prognosis for metastatic cancer patients despite extensive therapeutic efforts. Circulating tumor cells (CTCs), which detach from primary tumors and enter the bloodstream, can establish distant metastatic sites. These CTCs often form heterotypic clusters with white blood cells, especially neutrophils, through various interaction mechanisms, including intercellular adhesion, cytokine secretion, protease release, and the formation of neutrophil extracellular traps (NETs). These interactions enhance CTCs survival, proliferation, invasion, and transendothelial migration while simultaneously remodeling premetastatic niches and the tumor microenvironment. Consequently, pharmacologically disrupting CTC‒neutrophil crosstalk represents a promising strategy to curb metastatic spread and improve clinical outcomes. Recent breakthroughs in nanotechnology-based drug delivery systems have shown considerable potential in antimetastatic therapies, offering significant advantages over conventional treatments, which are often associated with severe side effects and limited efficacy. This review systematically explores nanoengineered strategies targeting CTC‒neutrophil interactions, addresses the current limitations and outlines future directions for developing clinically translatable nanotherapeutics. Graphical Abstract